Current and developing synthetic pharmacotherapy for treating relapsed/refractory multiple myeloma. (24th July 2017) - Podar, Klaus; Pecherstorfer, Martin
ABSTRACT: Introduction : The introduction of novel agents has significantly improved multiple myeloma (MM) patient outcome during the last two decades. MM received the most drug approvals for any one malignancy during this time period, both in the United States as well as in Europe. Areas covered : Proteasome inhibitors, immunomodulatory drugs, and monoclonal antibodies are prototype drug classes, which target both specific MM cell functions, as well as the tumor supportive bone marrow microenvironment, and represent current cornerstones of MM therapy. Importantly, the unprecedented extent and frequency of durable responses, in relapsed/refractory multiple myeloma (RRMM), in particular, is predominantly based on the combinatorial use of these agents with conventional chemotherapeutics or representatives of other drug classes. This article will summarize past landmark discoveries in MM that led to the dramatic progress of today's clinical practice. Moreover, developing strategies will be discussed that are likely to yet improve patient outcome even further. Expert opinion : Despite significant therapeutic advancements, MM remains an incurable disease. With several novel agents in the preclinical and early clinical pipeline, among those novel CD38 and BCMA mAbs, immune checkpoint inhibitors, as well as ricolinostat, selinexor, venetoclax, CAR-T cells, and vaccines, further advances in MM patient outcome are expected in the near future.